The effect of transfer pricing regulations on intra-industry trade - Vincent Dekker; Kristina Strohmaier (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
We analyse the effect of transfer pricing regulations on trade ows. We base our estimation on a panel gravity model, where the transfer pricing regulations are modeled as trade costs. To abstract from any aggregate demand shocks, we focus on intermediate goods in the car industry. Our results suggest a significant volume effect on the exported quantity as a result of the introduction of transfer pricing laws in the exporting country. Exports to lower tax rate countries are reduced, whilst exports to higher tax rate countries are increased. In line with theory, transfer pricing regulations only play a role if a tax rate difference exists between the trading partners.
urn:nbn:de:bsz:100-opus-14318
Keywords: F23; H25; H26; 330; Panel Gravity Model; Transfer Pricing Regulations; Intermediate Goods Trade; Corporate Tax